Metastatic inflammatory myofibroblastic tumor of the bladder - Libby, Emma K. (Urol Case Rep, 2018)
A 61-year-old male presented with gross hematuria and transurethral resection of bladder tumor revealed inflammatory myofibroblastic tumor (IMT). Due to extent of disease leading to ureteral obstruction and hydronephrosis, radical cystectomy (RC) with ileal conduit urinary diversion was performed. Five months after RC, the patient presented with decreased urine output. Exploratory laparotomy revealed mass in right colon and right hemicolectomy revealed metastatic IMT to the bowel and pericolonic fat. To our knowledge, this is the first report of primary IMT of the bladder metastasizing to other organs.